SOCIALIST INTERNATIONALISM AND THE PROBLEM OF INFORMATION (BUENOS AIRES, 1890-1930) - Buonuome, Juan (Revista de Historia Social y de las Mentalidades, 2022)
This article analyzes the information practices carried out by Argentine socialism and examines its role in the construction of socialist internationalism between 1890 and 1930. Based on a examination of the international coverage carried out by the newspaper La Vanguardia, and documents from different archives, it is argued that information constituted a practical problem of significant relevance in the golden years of socialist internationalism insofar as it established the terms and scope of transnational cooperation and solidarity from a peripheral space such as the South American Atlantic.
Keywords: Internationalism; Socialism; History of Communication; Periodical Press